Slaughter and Carcass Characteristics of Norduz Male Kids Raised in Either Intensive or Pasture Conditions - Daskiran, Irfan; Kor, Askin; Bingol, Mehmet (Pakistan Journal of Nutrition, 2006)
The aim of this study was to determine of the slaughter and carcass characteristics of Norduz male kids raised in either intensive or pasture conditions. Hot and chilled carcass dressing percentages in intensive and pasture groups were appeared to be 42.94±0.484 % and 41.49±0.503 %; 46.26±1.050 % and 44.63±1.03 %, respectively. In intensive and pasture groups, the omental fat and heart-lungs-liver proportions at slaughter weight of kids were determined as 1.18±0.209 %, 0.29±0.065 %; 4.75±0.107 %, 4.08±0.134 %, respectively. The kidney-knob and pelvic fat proportions at left half carcass weight were determined as 2.05±0.196 % for kids raised in intensive conditions and 1.06±0.182 % for kids raised in pasture conditions. In the rack joints, the lean portions of the intensive group and pasture group kids were 46.42±0.892 % 50.50±1.990 %, respectively. Total fat portions which contain subcutaneous fat and intermuscular fat were determined as 10.05±1.020 % in intensive group and 4.16±0.477 % in pasture group. In this study, it was concluded that; pasture group kids had similar slaughter and carcass characteristic values as intensively raised ones due to the special environmental condition and rich flora of the mentioned Norduz region of Van province.